Differential gene expression is not required for facultative sex allocation: a transcriptome analysis of brain tissue in the parasitoid wasp Nasonia vitripennis - Cook, Nicola (R Soc Open Sci, 2018)
Whole-transcriptome technologies have been widely used in behavioural genetics to identify genes associated with the performance of a behaviour and provide clues to its mechanistic basis. Here, we consider the genetic basis of sex allocation behaviour in the parasitoid wasp Nasonia vitripennis. Female Nasonia facultatively vary their offspring sex ratio in line with Hamilton's theory of local mate competition (LMC). A single female or ‘foundress’ laying eggs on a patch will lay just enough sons to fertilize her daughters. As the number of ‘foundresses’ laying eggs on a patch increases (and LMC declines), females produce increasingly male-biased sex ratios. Phenotypic studies have revealed the cues females use to estimate the level of LMC their sons will experience, but our understanding of the genetics underlying sex allocation is limited. Here, we exposed females to three foundress number conditions, i.e. three LMC conditions, and allowed them to oviposit. mRNA was extracted from only the heads of these females to target the brain tissue. The subsequent RNA-seq experiment confirmed that differential gene expression is not associated with the response to sex allocation cues and that we must instead turn to the underlying neuroscience to reveal the underpinnings of this impressive behavioural plasticity.